Efektifitas Badan Penanggulangan Bencana Daerah (BPBD) Dalam Pelaksanaan Program Kelurahan Siaga Becana Di Kota Semarang - Mughron, Maulana Mufis; Hariani, Dyah; Djumiarti, Titik (Journal of Public Policy and Management Review, 2016)
Semarang’s Regional Board for Disaster Management (Badan Penanggulangan Bencana Daerah or BPBD) is the board which holds the responsibility for disaster management in Semarang. In the disaster management effort in Semarang, Semarang’s BPBD develops disaster risk reduction program based on the society as the primary doer in 23 villages which have more chance of disaster in Semarang. This study is a descriptive qualitative study and collects the data through interview, observation, and document. The informants in this study are the people who have the knowledge of nature phenomenon or problem in implementation of disaster preparedness village. In this study, the writer uses effectiveness measurement theory by Duncan. From that measurement, the implementation of disaster preparedness village in Semarang still has some problems. The problems are the lack of attachment or time limit, the lack of real participation of private party in reducing disaster risk, the limit of supporting facilities for disaster preparedness village, the limit of rescuer team, the lack youth’s disaster awareness, and the unavailability of disaster management rule in the village. Based on the study result, it could be concluded that the implementation of disaster preparedness village in Semarang is not effective yet. Therefore, it is expected that there will be improvement in implementing of disaster preparedness village, especially the improvement of disaster preparedness village quality, authority cooperation, the employee, and supporting policy making in the village.